Tafsir Kontekstual Qs. Al-Baqarah Ayat 178: Rekonstruksi Qishas dan Pemaafan dalam Perspektif Keadilan Restoratif di Indonesia - Samaun Samaun (Lembaga Pengembangan Kinerja Dosen, 2026)
Al-Baqarah verse 178 regulates the legal mechanism of qishas as the maximum sanction for the criminal act of murder, while simultaneously opening space for forgiveness through the mechanisms of 'afwu and diyat. This verse is often understood partially and retributively, creating a negative impression of the Qur'an as merely emphasizing vengeance. This article re-examines the verse using a contextual tafsir approach to reconstruct an understanding of qishas that is not only retributive in dimension, but also restorative and humanistic. Employing the contextual tafsir method and the maqashid al-syari'ah approach, particularly hifz al-nafs as the primary objective of sharia, this study analyzes the semantic structure and asbab al-nuzul of the verse. The findings indicate that the phrase